Предмет: Математика, автор: damaratskayav

помогите пожалуйста
-6,6:(2 4/7+1/7•(-1,5))-2 17/85

Ответы

Автор ответа: абл
1

Ответ:

-5

Пошаговое объяснение:

-6,6:(2\frac{4}{7} +\frac{1}{7} * (-1,5))-2\frac{17}{85}=\\\\-\frac{33}{5}:(\frac{18}{7}+\frac{1}{7}*(-\frac{3}{2}))-\frac{187}{85}=\\\\ -\frac{33}{5}:(\frac{18}{7} +\frac{1}{7}*(-\frac{3}{2} ))-\frac{187}{85}=\\\\ -\frac{33}{5}:\frac{33}{14} -\frac{187}{85}=\\\\ -\frac{33}{5}*\frac{14}{33}-\frac{187}{85}=\\\\ -\frac{1}{5} *14-\frac{187}{85}=\\\\ -\frac{14}{5}-\frac{187}{85}=\\\\ -\frac{14}{5} -\frac{11}{5}=\\\\\frac{-14-11}{5}=\\\\\frac{-25}{5} =\\\\-\frac{25}{5}=\\\\-\frac{5}{1}=\\\\-5

Похожие вопросы